Structural Design Analysis of an Apartment Using a Flat Slab System with Prestressed Slabs - RIVI FATHURRACHMAN AZIS; Wahyu Kartini; Sumaidi (Racic : Rab Construction Research, 2025)
Pakuwon Residence Apartment is one of the high-rise buildings supporting vertical housing infrastructure in Bekasi City, West Java. The building employs a conventional structural system (slab, beam, and column). By using a flatslab system, the height of high-rise buildings is reduced because the ceiling height of each floor can be maximized. The disadvantage of the flatslab system is significant horizontal displacement; therefore, reinforcement with drop panels is necessary. Analysis was performed using the pushover method through dynamic analysis with the assistance of computer software. From the pushover analysis, the following results were obtained:Maximum displacement in the X direction is 41.085 mm (< 56 mm), Maximum displacement in the Y direction is 56.2925 mm (< 80 mm), Torsional irregularity is 1.155 (< 1.2), P-Delta effect is 0.0163 (< 0.1), Shear force is 21.21 MPa (≥ 2.92 MPa), Structural performance level is 0.0015 m and 0.0021 m (< 0.01), indicating the building is still classified as immediate occupancy (IO), Ductility is 2.94 (in the X direction) and 1.99 (in the Y direction), and classifying it as partial ductility.